SGLT-2 inhibitors: a step forward in the treatment of heart failure with reduced ejection fraction - Silva-Cardoso, José (2021)
© Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. This is an open access article under the CC-BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)